Molecular and ampelographic characterization of Pisco grapevine accessions conserved in a germplasm collection center of the Ica, Peru = Caracterización molecular y ampelográfica de accesiones de vides pisqueras conservadas en un centro de colección de germoplasma de Ica, Perú - Almanza Cano, Aybel; Cáceres Yparraguirre, Hanna; Torres, Maria Del Rocio; Saravia Navarro, David; Blas Sevillano, Raúl (Facultad de Ciencias Agropecuarias, Universidad de Trujillo (Perú), 2022)
Pisco is a distillate of cultural and economic importance for Peru, made from heterogeneous vine varieties called "pisqueras", covered by a Pisco Denomination of Origin legislation. The aim was to confirm the varietal identity of eight accessions conserved in the Germplasm Collection of the Centre for Productive Innovation and Technology Transfer Agroindustrial Ica (CITEagroindustrial), using 9 standardized microsatellite loci (SSR) and 14 morphological descriptors according to the International Organisation of Vine and Wine (OIV) to identify grapevine varieties. The SSR molecular profiles of 7 accessions were identified as varieties registered in the Vitis International Variety Catalog (VIVC) and only one had no association. Of these, Mollar, Albilla, Italia, Quebranta and Uvina accessions, were associated with Mollar Cano (VIVC 7901), Palomino Fino (VIVC 8888), Muscat of Alexandria (VIVC 8241), Quebranta (VIVC 9840) and Jacquez (VIVC 5627), respectively. The SSR profile of the Torontel accession was not associated with any variety registered in the VIVC and the Negra Criolla and Moscatel accessions were associated with the Spanish variety Listan Prieto (VIVC 6860). According to the ampelographic observations, it was determined that Moscatel presented phenotypic variations with respect to Negra Criolla, although at the molecular level it was perfectly associated with Listan Prieto, indicating that it would be a clonal variation. In addition, 7 variables were discriminant to identify the accessions evaluated. The molecular and ampelographic analysis allowed to clarify the varietal identity of the accessions conserved at CITEagroindustrial, Ica, which plays a preponderant role as a reference regarding the identification of the varieties used for the elaboration of Pisco in Peru.